PERLINDUNGAN HUKUM TERHADAP PRODUK USAHA MIKRO KECIL DAN MENENGAH TERKAIT MEREK YANG TIDAK TERDAFTAR DI INDONESIA - Ramadhani, Tasya (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The research objective is to offer protection for Micro, Small and Medium Enterprises products that are not registered with the Director General of Intellectual Property Rights. Using normative research based on the Legislative Approach and Conceptual Approach. Through this research the author offers the importance of brands in Micro, Small and Medium Enterprises and the protection of a product of Micro, Small and Medium Enterprises that has not been registered. There are a lot of Micro, Small and Medium Enterprises in Indonesia, moreover Micro, Small and Medium Enterprises in Indonesia are very influential in the Indonesian economy. Not only developing domestically, but Micro, Small and Medium Enterprises in Indonesia are also very developed abroad. The number of Micro, Small and Medium Enterprises in Indonesia has also led to the emergence of many products and brands. One Micro Small and Medium Enterprise with another Micro Small and Medium Enterprise may not have the same brand name. If there is a problem then in this case it will be a problem who first uses the brand name. The Constitutive System in Indonesia lacks legal certainty regarding trademark rights, in Indonesia it should use legal protection "Proving that the mark has been used in trade activities" and "Willing to be used in trading activities". And Micro, Small and Medium Enterprises must know how important the mark is to get a protection and the government must socialize the registration of the mark